The determinants of performance in master swimmers: a cross-sectional study on the age-related changes in propelling efficiency, hydrodynamic position and energy cost of front crawl - Zamparo, P.; Dall'Ora, A.; Toneatto, A.; Cortesi, M.; Gatta, G. (European Journal of Applied Physiology, 2012)
The decrease in swimming performance (v max) that occurs with age is a not only consequence of the physiological decrease in maximal metabolic power ( Emax ) but can also be expected to depend on an increase in the energy cost of swimming (C) Vmax=Emax/C. In turn, for a given speed and stroke C = W d / (npno) where W d is hydrodynamic resistance, np is propelling efficiency and no is overall efficiency. The aim of this study was to measure C in 47 male masters (31-85 years old) swimming the front crawl at sub-maximal, aerobic, speeds. During the experiments propelling efficiency and projected frontal area (A eff, an index of W d) were also determined by kinematic analysis. "Elder" masters (60-80 years) swam at a significantly slower pace (0.65 vs. 0.91 m/s), with a lower np (0.23 vs. 0.31) and a larger A eff (0.39 vs. 0.23 m2) than "younger" masters (30-60 years). No significant differences in C (1.45 kJ/m, on the average) were observed as a function of age or speed, but C values were significantly higher than those assessed in young elite swimmers at the very same speeds; the difference increasing with age with a rate of 0.75 % per year. With the due considerations (in this study the observed changes in np, A eff and C can be either attributed to changes in speed or age) these data confirm the hypothesis that an increase in C contributes to the decrease in swimming performance that occurs with age.